Average Error: 29.9 → 0
Time: 11.9s
Precision: 64
$\frac{\frac{{x}^{2}}{{x}^{6}}}{x}$
${x}^{\left(\left(2 - 6\right) - 1\right)}$
\frac{\frac{{x}^{2}}{{x}^{6}}}{x}
{x}^{\left(\left(2 - 6\right) - 1\right)}
double f(double x) {
double r26177877 = x;
double r26177878 = 2.0;
double r26177879 = pow(r26177877, r26177878);
double r26177880 = 6.0;
double r26177881 = pow(r26177877, r26177880);
double r26177882 = r26177879 / r26177881;
double r26177883 = r26177882 / r26177877;
return r26177883;
}


double f(double x) {
double r26177884 = x;
double r26177885 = 2.0;
double r26177886 = 6.0;
double r26177887 = r26177885 - r26177886;
double r26177888 = 1.0;
double r26177889 = r26177887 - r26177888;
double r26177890 = pow(r26177884, r26177889);
return r26177890;
}



# Try it out

Results

 In Out
Enter valid numbers for all inputs

# Derivation

1. Initial program 29.9

$\frac{\frac{{x}^{2}}{{x}^{6}}}{x}$
2. Using strategy rm
3. Applied pow129.9

$\leadsto \frac{\frac{{x}^{2}}{{x}^{6}}}{\color{blue}{{x}^{1}}}$
4. Applied pow-div0.1

$\leadsto \frac{\color{blue}{{x}^{\left(2 - 6\right)}}}{{x}^{1}}$
5. Applied pow-div0

$\leadsto \color{blue}{{x}^{\left(\left(2 - 6\right) - 1\right)}}$
6. Final simplification0

$\leadsto {x}^{\left(\left(2 - 6\right) - 1\right)}$

# Reproduce

herbie shell --seed 1
(FPCore (x)
:name "(pow(x,2)/pow(x,6))/x"
(/ (/ (pow x 2.0) (pow x 6.0)) x))